1995
DOI: 10.1089/thy.1995.5.283
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Subclinical Hypothyroidism

Abstract: Alterations in peripheral nerves are well documented in overt myxedema but not in subclinical hypothyroidism. We performed electrophysiologic studies to investigate such abnormalities in patients with normal serum total T4 and hyperresponsiveness of TSH to TRH, either with normal or high levels of basal circulating TSH. Subjects were divided in three groups: (i) Hypothyroidism Stage I (group () (n = 17, mean age = 39 +/- 34 years), T4 = 9 +/- 0.7 micrograms/dL, TSH = 4.3 +/- 0.4 microU/mL, sTSH post-TRH (peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 15 publications
0
22
0
5
Order By: Relevance
“…The electrophysiological abnormalities such as slowing of motor and sensory nerve conduction velocities have been reported in overt hypothyroidism [6][7][8][25][26][27]. Misiunas et al [28] and Ozata et al [11] recorded no significant differences between patients with subclinical hypothyroidism and a control group in distal latencies and motor conduction velocities of peripheral nerves. In the present study, the PNS was affected in 52% of the cases, entrapment neuropathy was the commonest (35%), which may be due to mucinous deposits that cause nerve compression.…”
Section: Discussionmentioning
confidence: 97%
“…The electrophysiological abnormalities such as slowing of motor and sensory nerve conduction velocities have been reported in overt hypothyroidism [6][7][8][25][26][27]. Misiunas et al [28] and Ozata et al [11] recorded no significant differences between patients with subclinical hypothyroidism and a control group in distal latencies and motor conduction velocities of peripheral nerves. In the present study, the PNS was affected in 52% of the cases, entrapment neuropathy was the commonest (35%), which may be due to mucinous deposits that cause nerve compression.…”
Section: Discussionmentioning
confidence: 97%
“…[13] Though fatty liver was present, none of the subjects had any evidence of cardiac disease or other sequelae of atherosclerosis.Nerve conduction studies had demonstrated presence of peripheral neuropathies in individuals with subclinical hypothyroidism. [15] Painful neuropathies and neuromuscular abnormitieswere reported to be relieved with hormone replacement therapies. [16,26] The most frequent presenting complaint in this study was body pains.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Increased rate of residual myocardial ischemia is also seen in patients with clinical hypothyroidism. [14] In the neuromuscular system subclinical hypothyroidism may cause peripheral neuropathies [15,16] muscular weakness and low exercise tolerance. [17] Reviews have also stated a significant prevalence of subclinical hypothyroidism among patients with bipolar mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…neurological and psychiatric or psychological, and coagulopathies. 10,[12][13][14][15] Atherosclerosis is a chronic process involving both cellular and humoral responses. In atherogenesis, leucocytes are involved in the early phase of atherosclerosis and maintain their activity during plaque formation, during which time sICAM-1 and sVCAM-1 first co-ordinate leucocyte adhesion, then their transendothelial migration.…”
Section: Discussionmentioning
confidence: 99%